What Can Speaking English Community Club Do with Student’s English Performance? (A Case Study at MTsN 1 Makassar) - Yusvita, Lavenia; Atmowardoyo, Haryanto; Samtidar, Samtidar (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2024)
This research aims to determine how the English club affects student’s English language skills at MTSN 1 Makassar. Data collection was carried out using observation checklists and interviews. This research was conducted using the case study and then concluded using the qualitative descriptive method. Participants in this research were students who joined the English club MTSN 1 Makassar. Based on the results of this research, the researcher found that the English club influenced student’s English language skills. Through the activities and motivation that are formed and the benefits that students can experience, it was found that the English club influenced students' English language skills to become better. Still, apart from that, several obstacles were also found that greatly influenced students' interest in learning, thus affecting their interest in learning to improve their abilities in the English language.